mTORC1 signaling in hepatic lipid metabolism - Jinbo Han (Protein & Cell, 2017)
ABSTRACT The mechanistic target of rapamycin (mTOR) signaling pathway regulates many metabolic and physiological processes in different organs or tissues. Dysregulation of mTOR signaling has been implicated in many human diseases including obesity, diabetes, cancer, fatty liver diseases, and neuronal disorders. Here we review recent progress in understanding how mTORC1 (mTOR complex 1) signaling regulates lipid metabolism in the liver.